To correct or to cooperate: Mediational processes and L2 development. (May 2020) - Poehner, Matthew E.; Leontjev, Dmitri
The present article argues for a conceptual distinction between corrective feedback and mediation that emphasizes the status of the latter not as an instructional practice but as a defining feature of human psychology (Vygotsky, 1987) that has direct implications for how instruction might be approached. Specifically, Sociocultural Theory (SCT) posits that humans are always and everywhere mediated, as individuals draw upon meanings and ways of thinking they have already internalized as well as those that are available in their immediate environment to regulate their actions. With regard to second language (L2) education, rather than exclusively focusing on learner independent performance or whether learners improve following application of a particular corrective feedback strategy, a view of learner performance as a mediated process draws attention to changes – either over the course of an activity or from one activity to the next – to the degree of guidance learners require and the ways in which they respond to or negotiate that support. This mediation process, the changes that may be observed, and how these may be interpreted vis-à-vis learner development is illustrated with examples taken from two recent Dynamic Assessment (DA) studies involving Estonian learners of L2 English. The first study focuses upon one-to-one dialogic interaction in an individualized DA program while the second study reports the implementation of a computerized DA procedure ( n = 25). Together, they underscore how the goal of promoting learner L2 development through instruction may be advanced when mediational processes are taken into account and learner developmental trajectories are identified. Implications of mediational processes for future work interested in corrective feedback are discussed.